Neutrophils Modulate Fibrogenesis in Chronic Pulmonary Diseases - Ding, Lili; Yang, Juan; Zhang, Chunmei; Zhang, Xiuna; Gao, Pujun (Frontiers in Medicine, 2021)
Chronic inflammatory pulmonary diseases are characterized by recurrent and persistent inflammation of the airways, commonly with poor clinical outcomes. Although their etiologies vary tremendously, airway neutrophilia is a common feature of these diseases. Neutrophils, as vital regulators linking innate and adaptive immune systems, are a double-edged sword in the immune response of the lung involving mechanisms such as phagocytosis, degranulation, neutrophil extracellular trap formation, exosome secretion, release of cytokines and chemokines, and autophagy. Although neutrophils serve as strong defenders against extracellular pathogens, neutrophils and their components can trigger various cascades leading to inflammation and fibrogenesis. Here, we review current studies to elucidate the versatile roles of neutrophils in chronic pulmonary inflammatory diseases and describe the common pathogenesis of these diseases. This may provide new insights into therapeutic strategies for chronic lung diseases.